STRATEGI PENGEMBANGAN MODAL SOSIAL UNTUK PENINGKATAN KEBERDAYAAN PETANI KARET DI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Rian Irawan; Ahmad Rifai; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to: 1) analyzes the social capital of the farmer rubber, 2) Analyze empowerment rubber farmers, 3) analyzed the Relationship of social capital and peasant empowerment rubber, 4) Formulating strategies to social capital development empowerment farmer rubber in district Tambusai North. This research was conducted in Northern Tambusai. Social capital measured by analysis of Principal Component Analysis (PCA) and the Likert scale, the relationship between social capital and keberdayaan rubber farmers using correlation analysis of rank spearman and formulate social capital for rubber farmers with empowerment using SWOT analysis. The results show that social capital has a specific relationship with high intensity on individuals in the group are at high intensity. Empowerment generated by five elements: land, pengelolahan land, seeds, maintenance, and production in the category quite helpless. A significant relationship, correlated positively and weak direction occur between social capital against farmers empowerment rubber.Keywords: social capital, empowerment, rubber farmer